FOREIGN EXPERIENCE IN CLUSTERIZATION DEVELOPMENT (Marketing Journal, 2025)
This article examines international experience in the development of clustering. It analyzes cluster development models employed in various countries and their impact on enhancing the competitiveness of different industries. Key factors for the successful functioning of clusters are considered, including government support, innovative technologies, and cooperation among participants. Promising directions for adapting foreign experience to domestic agricultural policy have been identified.
Keywords: clustering; competitiveness; international experience; agricultural technologies; cooperation; government support; SEZ; export; import; investment